Thick film resistor paste, thick film resistor, and electronic component

A thick film resistance paste with specific glass and oxide compositions addresses surge resistance issues in miniaturized resistors by ensuring uniform conductor distribution and controlled TCR, enhancing their performance under surge conditions.

JP7622737B2Active Publication Date: 2025-01-28SUMITOMO METAL MINING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022518160
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-01
Filing Date
2021-04-30
Publication Date
2025-01-28
Estimated Expiration
2041-04-30

AI Technical Summary

Technical Problem

Thick film resistors in electronic components face challenges in achieving high surge resistance due to localized heating and resistance value changes when subjected to surge voltages, and increasing the content of ruthenium dioxide leads to increased resistance temperature coefficient (TCR), limiting their performance.

Method used

A thick film resistance paste composed of ruthenium-containing glass powder with specific ratios of silicon oxide, lead oxide, and boron oxide, along with other additives, is used to form a thick film resistor with improved surge resistance and controlled TCR, ensuring uniform conductor distribution and reduced heat generation.

Benefits of technology

The solution provides thick film resistors with enhanced surge resistance and controlled TCR, maintaining consistent resistance values under surge conditions, suitable for miniaturized electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622737000001
    Figure 0007622737000001
  • Figure 0007622737000002
    Figure 0007622737000002
  • Figure 0007622737000003
    Figure 0007622737000003
Patent Text Reader

Abstract

[Problem] To provide: a thick film resistor paste for use in resistors that are for electronic components, which continue being miniaturized, and that have sufficient anti-surge characteristics and a smaller resistance change rate; a thick film resistor using the thick film resistor paste; and an electronic component comprising said thick film resistor. [Solution] The present invention comprises an organic vehicle and a ruthenium lead oxide-containing glass powder. The ruthenium lead oxide-containing glass powder comprises 10-70 mass% of ruthenium lead oxide. The glass composition comprises, per 100 mass% of the glass component, 3-60 mass% of silicon oxide, 30-90 mass% of lead oxide, and 5-50 mass% of boron oxide. The total content of silicon oxide, lead oxide and boron oxide is at least 50 mass% with respect to 100 mass% of the glass component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thick-film resistor paste, and more specifically, to a thick-film resistor paste that contains glass powder containing lead ruthenate as a conductive material and that can form a thick-film resistor having particularly excellent surge resistance, a thick-film resistor using the thick-film resistor paste, and an electronic component equipped with the thick-film resistor. [Background technology]

[0002] A thick-film resistor paste is generally composed of conductive powder, glass powder, and an organic vehicle for forming them into a paste suitable for printing. This thick-film resistor paste is printed in a desired pattern, and the glass is sintered at a high temperature of usually 800 to 1000°C, and is used as a thick-film resistor that constitutes an electronic component such as a thick-film chip resistor. Ruthenium oxide powder and lead ruthenate powder are widely used as the conductive powder, since the resistance value can be changed gradually by adjusting the mixing ratio with the glass powder.

[0003] For example, Patent Document 1 discloses a resistor obtained by adding a vehicle using ethyl cellulose as a binder and toluene and alcohol as a solvent to a mixture using mullite as inorganic particles, lead borosilicate glass as glass particles, and ruthenium dioxide as conductive particles. Anti-pe The technology for forming thick film resistors using a paste is described.

[0004] Patent Document 2 describes a resistor obtained by adding a vehicle using ethyl cellulose as a binder and terpineol and butyl carbitol acetate as a solvent to a mixture using zircon as inorganic particles, borosilicate lead glass as glass particles, and ruthenium dioxide as conductive particles. Anti-pe The technology for a thick-film resistor formed using the resistive paste is also described.

[0005] In recent years, electronic components such as thick-film chip resistors have become smaller, and thick-film resistors are required to have improved electrical properties. In particular, thick-film resistors with excellent voltage resistance, such as surge resistance, are required. When a momentary high voltage (surge voltage) is applied to a thick-film resistor, it usually shows a negative resistance change, but it is desirable for this resistance change to be small. Such a negative resistance change is thought to be the effect of heat generation when voltage is applied. In conventional thick-film resistor pastes, glass powders are bonded together during sintering, but the softening of the glass powder is limited to the surface layer. Therefore, in the thick-film resistor after sintering the thick-film resistor paste, a dielectric layer equivalent to the glass particle diameter exists. The conductive powder is distributed around this dielectric layer, giving the thick-film resistor conductivity. It is thought that when a surge voltage is applied to such a structure, a current flows through the conductive part, the surrounding area is locally heated, and a resistance change occurs.

[0006] One method for improving the surge resistance of thick-film resistors is to increase the amount of lead ruthenate contained in the thick-film resistor paste. By increasing the amount of lead ruthenate contained in the thick-film resistor paste, a thick conductive path and a strong conductive part are formed in the thick-film resistor after sintering the thick-film resistor paste, which is thought to suppress heat generation when a surge voltage is applied and mitigate the effect of changes in resistance value. However, increasing the amount of lead ruthenate increases the temperature coefficient of resistance (TCR). TCR indicates the rate of change in resistance per unit temperature, and is one of the important characteristics of thick-film resistors. If the TCR increases by increasing the amount of lead ruthenate, even if the change in resistance due to heat generation when a surge voltage is applied is suppressed, the resistance of the conductive part itself will change. For this reason, when increasing the amount of lead ruthenate, it is necessary to bring the TCR closer to 0. This TCR can be adjusted by adding an additive, mainly made of a metal oxide, to the thick-film resistor, and examples of the metal oxide include manganese oxide, niobium oxide, and titanium oxide. However, there is a limit to the degree to which the additive can be adjusted, and therefore there is also a limit to the amount of lead ruthenate that can be increased.

[0007] Another method for improving the surge resistance of thick-film resistors is to make the distribution of conductors in the resistor more uniform. If the distribution of conductors is made uniform, current will flow uniformly through the resistor when a surge voltage is applied, and the effect of localized heat generation can be mitigated. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-320003 [Patent Document 2] Japanese Patent Application Publication No. 6-163202 Summary of the Invention [Problem to be solved by the invention]

[0009] However, in recent years, thick-film resistors for electronic components have become increasingly smaller, and therefore higher surge resistance is required. An object of the present invention is to provide a thick-film resistor paste for resistors having a smaller rate of resistance change and excellent surge resistance for electronic components that are becoming increasingly smaller, a thick-film resistor using the thick-film resistor paste, and an electronic component equipped with the thick-film resistor. [Means for solving the problem]

[0010] As a result of various studies, the inventors of the present invention discovered that a thick-film resistor formed from a thick-film resistor paste using lead ruthenate-containing glass having a specific composition has better surge resistance than conventional thick-film resistors, and thus came up with the present invention.

[0011] That is, the thick-film resistor paste according to the present invention contains a lead ruthenate-containing glass powder and an organic vehicle, and the lead ruthenate-containing glass powder contains lead ruthenate in an amount of 10 mass % to 70 mass % and the glass composition contains silicon oxide in an amount of 100 mass % of the glass component. 33% or more by mass and 60% or less by mass of silicon oxide, 30% or more by mass and 90% or less by mass of lead oxide, and 5% or more by mass and 50% or less by mass of boron oxide, and the total content of silicon oxide, lead oxide, and boron oxide is 50% or more by mass relative to 100% by mass of the glass component.

[0012] In the thick-film resistor paste of the present invention, the lead ruthenate-containing glass powder preferably has an average particle size of 5 μm or less.

[0013] A thick film resistor according to the present invention is characterized in that it is made of a sintered body of any one of the thick film resistor pastes according to the present invention.

[0014] The electric / electronic device according to the present invention is characterized in that it comprises the above-mentioned thick-film resistor according to the present invention. Effect of the Invention

[0015] According to the present invention, it is possible to provide a thick-film resistor paste having better surge resistance than conventional thick-film resistors, a thick-film resistor using the thick-film resistor paste, and an electric / electronic device including the thick-film resistor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment within the scope of the present invention. The thick-film resistor paste of this embodiment contains a lead ruthenate-containing glass powder and an organic vehicle. Each component will be described in detail below.

[0017] (Conductive material) Lead ruthenate is used as the conductive material in the thick-film resistor paste of the present invention. A typical thick-film resistor paste has a structure containing a conductive material and glass in powder form, but the thick-film resistor paste of the present invention does not use lead ruthenate powder as the conductive material alone, but contains lead ruthenate-containing glass powder obtained by crushing lead ruthenate-containing glass produced using lead ruthenate powder as a conductive material as part of the raw material. The particle size of the lead ruthenate used to form the lead ruthenate-containing glass powder is not particularly limited, but it is preferable that the specific surface area is less than 5 m 2 It is desirable to have a particle size of 5 m / g or more. 2 If the particle size is less than 1.0 μm / g, the particle size of lead ruthenate is too large, which may reduce the uniformity of the conductive area in the thick-film resistor and deteriorate the surge resistance.

[0018] (Glass component) The glass component used in the lead ruthenate-containing glass in the thick-film resistor paste of the present invention contains silicon oxide (SiO2), lead oxide (PbO), and boron oxide (B2O3). In addition, magnesium oxide (MgO), calcium oxide (CaO), barium oxide (BaO), strontium oxide (SrO), cadmium oxide (CdO), tin oxide (SnO), zinc oxide (ZnO), bismuth oxide (Bi2O3), etc. may be contained. Aluminum oxide (Al2O3) may also be contained.

[0019] (Silicon oxide: SiO2) SiO2 is a component that forms the framework of the glass component of the present invention, and its blending amount is 3% by mass or more and 60% by mass or less with respect to 100% by mass of the glass component contained in the lead ruthenate-containing glass. If it is more than 60% by mass, the softening point of the glass formed will be too high. If it is less than 3% by mass, a chemically stable glass cannot be obtained.

[0020] (Lead oxide: PbO) In addition to lowering the softening point, PbO also serves to chemically stabilize lead ruthenate and inhibit its decomposition. The amount of PbO blended is 30% to 90% by mass relative to 100% by mass of the glass components contained in the lead ruthenate-containing glass. If it is less than 30% by mass, the softening point of the glass formed will be too high. If it is more than 90% by mass, it will be difficult to obtain a chemically stable glass state.

[0021] (Boron oxide: B2O3) B2O3, together with SiO2, is a component that forms the framework of the glass component of the present invention, and has the effect of lowering the softening point of the glass formed. The blending amount is 5% by mass or more and 50% by mass or less with respect to 100% by mass of the glass component contained in the lead ruthenate-containing glass. If it is less than 5% by mass, the toughness of the glass formed decreases, cracks tend to occur, and the laser trimming properties deteriorate. If it is more than 50% by mass, phase separation of the glass component tends to occur, and water resistance also decreases.

[0022] (Total content of essential glass components) The total content of SiO2, PbO, and B2O3 is 50% by mass or more relative to 100% by mass of the glass components contained in the lead ruthenate-containing glass. If the total content is less than 50% by mass, it is difficult to stably form the glass, and it is difficult to obtain satisfactory surge resistance as an electrical characteristic of the thick-film resistor of the present invention.

[0023] (Other glass components) In addition to the above essential glass components, oxides may be further contained as glass components to improve various properties, within the range that does not deteriorate the properties of the lead ruthenate-containing glass. Specifically, Al2O3, MgO, CaO, BaO, SrO, CdO, SnO, ZnO, Bi2O3, etc. may be contained. The blending amount of these glass components is 20 mass% or less for each of 100 mass% of the glass components contained in the lead ruthenate-containing glass.

[0024] (Lead ruthenate-containing glass) In the lead ruthenate-containing glass used in the thick-film resistor paste of the present invention, the mixing ratio of the conductive lead ruthenate and the glass component is 10% by mass to 70% by mass of lead ruthenate and 30% by mass to 90% by mass of the glass component, relative to 100% by mass of the lead ruthenate-containing glass composition. If the lead ruthenate content is less than 10% by mass, the resistance value of the produced lead ruthenate-containing glass powder becomes too high and it shows almost no conductivity. If the content is more than 70% by mass, the glass component cannot cover the lead ruthenate powder, and the lead ruthenate-containing glass becomes brittle. By adjusting the mixing ratio of the lead ruthenate and the glass component, it is possible to adjust the resistance value of the thick-film resistor to the vicinity of the target resistance value. The lead ruthenate-containing glass is pulverized to an average particle size of 5 μm or less. If the average particle size is larger than 5 μm, the uniformity of the thick-film resistor decreases, and there is a risk that the improvement in surge resistance cannot be obtained, which is not preferable. The pulverization method can be a ball mill, a planetary mill, a bead mill, etc. In the present invention, the average particle size means the median diameter, and is a value measured by ultrasonically dispersing the powder to be measured in a 2 g / L aqueous solution of sodium hexametaphosphate and using a particle size distribution meter (HPA9320-100X, manufactured by Microtrackbell) using pure water as a solvent.

[0025] (Other additives) The thick-film resistor paste of the present invention may further contain borosilicate glass that does not contain conductive materials and commonly used additives for the purpose of adjusting and improving the resistance value, TCR, and other characteristics of the thick-film resistor. In addition, a dispersant may be contained as an additive to improve dispersibility. Main additives include niobium oxide (Nb2O5), tantalum oxide (Ta2O5), titanium oxide (TiO2), copper oxide (CuO), manganese oxide (MnO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), etc. The content of the additive can be adjusted according to the desired improved characteristics, but it is preferably 10 mass% or less in the total amount of inorganic substances of 100 mass%.

[0026] (Organic Vehicle) The organic vehicle used in the thick-film resistor paste of the present invention is not particularly limited, and may be one in which a resin such as ethyl cellulose or rosin is dissolved in a solvent such as terpineol, which is used in general resistor pastes. The amount of the organic vehicle may be appropriately adjusted depending on the printing method, etc., but is generally 20% by mass or more and 50% by mass or less with respect to the total amount of the resistor paste, 100% by mass.

[0027] (Method of manufacturing thick film resistor paste) The method for producing a thick-film resistor paste by mixing the lead ruthenate-containing glass and the organic vehicle, and optionally adding lead borosilicate glass powder and additives, is not particularly limited, and a general three-roll mill, a bead mill, or the like can be used.

[0028] (Manufacturing method of thick film resistors) The obtained thick-film resistor paste is printed on a ceramic substrate, the organic solvent is removed by drying treatment, and then the substrate is fired at a temperature of, for example, 800° C. to 900° C. to obtain a thick-film resistor. EXAMPLES

[0029] The present invention will be described below in more detail with reference to examples, but the present invention is not limited to these examples.

[0030] Example 1: Evaluation of a resistor with a sheet resistance of 10 kΩ The glass material was mixed at a ratio of 63 mass% and lead ruthenate at 37 mass%, melted, and then cooled to prepare lead ruthenate-containing glass. The glass composition of the prepared lead ruthenate-containing glass was 33 mass% SiO2, 46 mass% PbO, 5 mass% Al2O3, 7 mass% B2O3, 3 mass% ZnO, and 6 mass% CaO relative to 100 mass% of the glass components. The obtained lead ruthenate-containing glass was pulverized in a ball mill to an average particle size of about 1 μm. A thick-film resistor composition containing 59% by mass of lead ruthenate-containing glass powder, 1% by mass of Nb2O5 as an additive, and the remainder being an organic vehicle was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare the thick-film resistor paste of Example 1. The organic vehicle used was a solution of 20 parts by mass of ethyl cellulose dissolved in 100 parts by mass of terpineol. The composition of the thick-film resistor paste of Example 1 and the composition of the lead ruthenate-containing glass used to manufacture the thick-film resistor paste are shown in Table 1.

[0031] <Evaluation test> (Preparation of evaluation samples) The thick-film resistor paste thus prepared was printed with a width of 1.0 mm between five pairs of electrodes spaced 1.0 mm apart on an alumina substrate in advance, and then dried in a belt furnace at a peak temperature of 150°C for 5 minutes. It was then fired in a belt furnace at a peak temperature of 850°C for 9 minutes. Five samples were prepared in the same manner, each for an alumina substrate, to obtain thick-film resistors (total of 25 pieces) for evaluation.

[0032] (film thickness measurement) The film thickness was measured by using a stylus-type surface roughness tester to randomly select one alumina substrate from the evaluation samples, measure the film thickness of each of the five thick-film resistors, and record the average value of the five points as the actual measured film thickness.

[0033] (Converted area resistance value) The resistance values ​​at 25°C of five evaluation samples (total of 25 samples) formed on five alumina substrates were measured using a circuit meter (2001 MULTIMETER, manufactured by KEITHLEY), and the average value was taken as the actual measured resistance value. The converted sheet resistance value when the film thickness was set to 7 μm was calculated using the following formula (1). The calculated converted sheet resistance values ​​are shown in Table 1. 3 As shown in. Converted sheet resistance (kΩ) = measured resistance (kΩ) × (measured film thickness (μm) / 7 (μm)) (1)

[0034] (High temperature coefficient of resistance: High temperature TCR) The resistance values ​​of five thick-film resistors formed as evaluation samples on a single alumina substrate were measured after being held in a thermostatic chamber at 25°C and 125°C for 30 minutes. The measured resistance values ​​were designated as R 25 , R 125 The high-temperature TCR was calculated using the following formula (2). The average value of the calculated high-temperature TCR at five points is shown in Table 3. High temperature TCR (ppm / ℃)=[(R 125 -R 25 ) / R 25 ] / (100)×10 6 (2)

[0035] (Evaluation of trimming ability) A glass material containing 30% by mass of SiO2, 55% by mass of PbO, 5% by mass of Al2O3, and 10% by mass of B2O3 was kneaded by a three-roll mill so as to be dispersed in an organic vehicle of the same composition as that used in Example 1, to prepare a glass paste. The glass paste was applied so as to cover the thick-film resistor of the evaluation sample, and dried in a belt furnace at a peak temperature of 150°C for 5 minutes. Then, the resistor was fired in a belt furnace at a peak temperature of 600°C for 5 minutes. The resistance value of the thick-film resistor covered with the glass paste was set to the initial resistance value Rs(t), and laser trimming was performed using a laser trimming device (SL432R, manufactured by Omron Laserfront Co., Ltd.) so as to obtain a resistance value 1.5 times that of Rs(t). The laser trimming conditions were straight cut, cut speed 100 mm / sec, laser intensity 2 W, and Q rate 6 kHz. The resistance value after trimming was designated as Re(t), and the percentage of the resistance value deviation before and after trimming was calculated using the following equation (3). Resistance deviation (%) = (Re(t) - 1.5 × Rs(t)) / Rs(t) × 100 (3) If even one of the five thick film resistors had a resistance value deviation of 1% or more, the trimming ability was rated as "X", and if all resistance value deviations were less than 1%, the ability was rated as "O". The evaluation results are shown in Table 3.

[0036] (Surge resistance evaluation: resistance change rate) When the trimming property was evaluated as "good", an electrostatic discharge test was performed on the thick-film resistor of the evaluation sample using a semiconductor device electrostatic tester (ESS-6008, manufactured by Noise Laboratory) to apply a voltage under the conditions of a capacitance of 200 pF and an internal resistance of 0 Ω. A voltage of 5 kV was applied to the thick-film resistor of the evaluation sample five times at one-second intervals, and the resistance value Rs before and the resistance value Re after the voltage application were measured, and the resistance change rate was calculated using the following formula (4). The average resistance change rate calculated at five points is shown in Table 3. Resistance change rate (%) = (Re-Rs) / Rs × 100 (4)

[0037] (Examples 2 to 12) Glass materials and lead ruthenate were mixed in the ratios shown in Table 1, melted, and then cooled to prepare lead ruthenate-containing glasses. The glass composition of each of the prepared lead ruthenate-containing glasses was as follows: SiO 2 , PbO, Al 2 O 3 、B 2 O 3 The contents of ZnO and CaO are as shown in Table 1. Each of the obtained lead ruthenate-containing glasses was pulverized in a ball mill to an average particle size shown in Table 1. A thick-film resistor composition containing the lead ruthenate-containing glass powder, additives, and organic vehicle in the ratios shown in Table 1 was kneaded in a three-roll mill so that the various inorganic materials were dispersed in the organic vehicle, to prepare the thick-film resistor pastes of Examples 2 to 12. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3. It should be noted that Examples 4, 7, 9, and 10 are reference examples.

[0038] Comparative Example 1 A thick-film resistor paste was prepared by a conventional manufacturing method in which lead ruthenate-containing glass was not used, and lead ruthenate and glass, which are conductive materials, were added in powder form. However, if lead ruthenate powder and glass powder were added without using lead ruthenate-containing glass powder obtained by crushing lead ruthenate-containing glass, differences in electrical characteristics (TCR) and the like would occur when adjusting the resistance value to suit the thick-film resistor paste. Therefore, in Comparative Example 1 prepared by a conventional manufacturing method, in order to adjust the TCR and the like, ruthenium oxide powder was also added as a conductive material in addition to lead ruthenate powder, and the blending amount was adjusted. That is, a thick-film resistor composition containing 6 mass% ruthenium oxide powder, 17 mass% lead ruthenate powder, 36% glass powder, 1 mass% Nb2O5 as an additive, and the remainder was an organic vehicle was prepared, and the mixture was kneaded by a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, and the thick-film resistor paste of Comparative Example 1 was prepared. The glass composition in the prepared thick-film resistor paste was 100% by mass of the glass component, with 33% by mass of SiO2, 47% by mass of PbO, 5% by mass of Al2O3, 7% by mass of B2O3, 3% by mass of ZnO, and 5% by mass of CaO. The organic vehicle had the same composition as that used in Example 1. The composition of the thick-film resistor paste in Comparative Example 1 and the composition of the glass used in the manufacture of the thick-film resistor paste are shown in Table 2. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.

[0039] Comparative Example 2 Glass containing 77% by mass and lead ruthenate containing 23% by mass were mixed and melted, and then cooled to produce lead ruthenate-containing glass. The glass composition of the conductive glass thus produced was 100% by mass of glass components, with 30% by mass of SiO2, 65% by mass of PbO, 2% by mass of Al2O3, and 3% by mass of B2O3. The obtained lead ruthenate-containing glass was pulverized in a ball mill to an average particle size of about 1 μm. A thick-film resistor composition containing 73 mass% lead ruthenate-containing glass powder, 1 mass% Mn2O3 as an additive, and the remainder an organic vehicle was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare a thick-film resistor paste of Comparative Example 2. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.

[0040] (Comparative Examples 3 to 10) Glass materials and lead ruthenate were mixed in the proportions shown in Table 1, melted, and then cooled to produce lead ruthenate-containing glasses. The glass composition of each of the lead ruthenate-containing glasses produced has the content ratios shown in Table 1 for SiO2, PbO, Al2O3, B2O3, ZnO, and CaO relative to 100 mass% of the glass component. Each of the obtained lead ruthenate-containing glasses was pulverized in a ball mill to have an average particle size shown in Table 1. A thick-film resistor composition containing the lead ruthenate-containing glass powder, additives, and an organic vehicle in the ratios shown in Table 1 was kneaded in a three-roll mill so that the various inorganic materials were dispersed in the organic vehicle, to prepare thick-film resistor pastes of Comparative Examples 3 to 10. The organic vehicle had the same composition as that used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.

[0041] [Table 1]

[0042] [Table 2]

[0043] [Table 3]

[0044] As shown in Table 3, the thick-film resistors of Examples 1 to 12 formed using the thick-film paste prepared using the lead ruthenate-containing glass powder of the present invention had a very low rate of change in resistance value before and after the electrostatic discharge test, and were found to have excellent surge resistance (high voltage resistance), compared to the thick-film resistor of Comparative Example 1 formed using the conventional thick-film resistor paste prepared without using the lead ruthenate-containing glass powder. In addition, the thick-film resistors of Comparative Examples 2, 6, 8, and 10, which were formed using thick-film resistor pastes obtained using lead ruthenate-containing glasses made using glass components with a boron oxide content lower than the range claimed in the present invention, were found to have insufficient trimming properties and were not suitable for commercialization. In addition, the thick-film resistor of Comparative Example 3 formed from a thick-film resistor paste obtained using a lead ruthenate-containing glass having a lead ruthenate content lower than the range of the present invention was found to have an excessively high resistance value of the lead ruthenate-containing glass powder and to have almost no conductivity. In addition, the thick-film resistor of Comparative Example 4, which was formed from a thick-film resistor paste obtained using a lead ruthenate-containing glass having a lead ruthenate content greater than the range of the present invention, was found to have a higher rate of change in resistance value before and after the electrostatic discharge test and to have inferior surge resistance compared to the thick-film resistors of Examples 1 to 12. Furthermore, the thick-film resistors of Comparative Examples 5 and 7, which were formed from thick-film resistor pastes obtained using glass components whose silicon oxide or lead oxide contents, or whose total contents of these essential glass components were outside the ranges of the present invention, and the thick-film resistor of Comparative Example 9, which was formed from a thick-film resistor paste obtained using a glass component whose boron oxide content was higher than the range of the present invention, also had a higher rate of change in resistance value before and after the electrostatic discharge test and were inferior in surge resistance compared to the thick-film resistors of Examples 1 to 12.

[0045] From the above test results, it is recognized that the thick film resistor formed using the thick film resistor paste of the present invention has excellent trimming properties and surge resistance, and can be suitably used for electronic components, which have become increasingly miniaturized in recent years.

Claims

1. The glass powder contains lead ruthenate and an organic vehicle. The lead ruthenate-containing glass powder contains lead ruthenate in an amount of 10% by mass or more and 70% by mass or less, The glass composition contains 33% by mass or more and 60% by mass or less of silicon oxide, 30% by mass or more and 90% by mass or less of lead oxide, and 5% by mass or more and 50% by mass or less of boron oxide, relative to 100% by mass of the glass component; The total content of silicon oxide, lead oxide, and boron oxide is 50% by mass or more based on 100% by mass of the glass component. A thick film resistor paste comprising:

2. 2. The thick-film resistor paste according to claim 1, wherein the lead ruthenate-containing glass powder has an average particle size of 5 [mu]m or less.

3. A thick film resistor comprising a sintered product of the thick film resistor paste according to claim 1 or 2.

4. An electric or electronic part comprising the thick film resistor according to claim 3.

Citation Information

Patent Citations

  • Resistor

    JP1977054195A

  • Method of manufacturing paste for resistance body

    JP1978100496A

  • Thick film resistor

    JP1992320003A

  • Thick film resistor paste and thick film resistor and manufacturing method thereof

    JP1994163202A